PREVALENCE AND CLINICAL PREDICTORS OF MEDICATION OVERUSE HEADACHES AMONG PATIENTS WITH PRIMARY HEADACHE DISORDERS: A PROSPECTIVE STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Medication Overuse Headache is an important and preventable issue in primary headache patients. Regular, unsupervised use of medicines used for acute pain may lead to an increase in headache frequency, increased headache-related disability and the progression to chronic headache. Patients suffering from migraine and other recurrent headache disorders are especially at risk if they take analgesics on a regular basis without medical supervision. Objective: To determine the prevalence and clinical predictors of medication overuse headache among patients with primary headache disorders. Methods: The study was a prospective study carried out in a hospital (Akbar Niazi Teaching Hospital, Islamabad) from 1st January 2025 to 15th January 2026. The patients were selected by the non-probability consecutive sampling technique to arrive at 352 patients with primary headache disorders. Demographic data, type of primary headache disorder, headache duration and frequency, headache severity, associate symptoms, sleep disturbances, self-medication, and type and frequency of medication use were collected. Patients with a pre-existing primary headache disorder were assessed for medication overuse headache based on the regular use of acute headache medication for over three months. Data were analysed by SPSS. Where applicable, the following tests were used: chi-square test, independent sample t-test, and binary logistic regression. A p value of < 0.05 was deemed statistically significant. Results: Out of 352 patients, medication overuse headache was present in 104 patients, giving a prevalence of 29.5%. Migraine was the most common primary headache disorder and was significantly associated with medication overuse headache. Patients with medication overuse headache were more likely to have headache frequency of ≥15 days per month, severe headache intensity, longer duration of headache illness, sleep disturbance, self-medication, and use of combination analgesics. On logistic regression analysis, headache frequency of ≥15 days per month, self-medication, migraine diagnosis, severe headache intensity, and use of combination analgesics were the strongest independent predictors. Conclusion: Medication overuse headache was common among patients with primary headache disorders, affecting nearly one-third of the study population. Frequent headache days, self-medication, migraine, severe headache intensity, and combination analgesic use were important predictors. Early recognition, patient counselling, avoidance of unsupervised analgesic use, and timely preventive treatment may help reduce the burden of medication overuse headache.